Multi-word-constructions and linguistic development in early foreign language classrooms: the role of input variability - Schulz, JM (2024)
Upon finishing FL learning at primary school, many students lack productive knowledge, for example regarding structures like verb-argument-constructions (e.g., [Verb] about [Noun]), indispensable for increasing communicative agency, as expected by curricula. These curricula adopt a usage-based constructionist approach to language learning and consider 'large linguistic units' (e.g., routines (How are you?) or patterns (My favourite _ is _)) to be catalysts for students' development of a productive linguistic repertoire. However, despite the ubiquity of such units in primary curricula, evidence on the impact of teaching input consisting of such structures on primary FL students’ linguistic development is scarce, as indicated by Schulz et al. (2023), reported in this thesis.